Peran Koperasi Peternakan Bandung Selatan (KPBS) Pangalengan dalam Pemberdayaan Peternak Sapi Perah (Kasus di TPK Cipanas Desa Margamukti Kecamatan Pangalengan Kabupaten Bandung Provinsi Jawa Barat) - Syahirul Alim; Fuzi Ridwan Firdaus; Unang Yunasaf (Fakultas Pertanian Universitas Jember, 2021)
The purposes of this research were to find out the role of KPBS Pangalengan in the empowerment of dairy farmers, the empowerment of dairy farmers in TPK Cipanas, and corelation between the role of KPBS Pangalengan with the empowerment of dairy farmers in TPK Cipanas. The research method was survey with questionnaires to 30 dairy farmers. The data obtained was analyzed by spearman rank analysis. The results showed that the role of cooperatives in the empowerment of dairy farmers was in the high category (63.33%), farmer empowerment in medium category (56.67%), and the correlation between the role of KPBS Pangalengan with the empowerment of dairy farmers in TPK Cipanas showed a positive relation with rs = 0.642. Keywords: Role of KPBS Pangalengan, Farmer Empowerment, Dairy Cows